The Implementation of Project-Based Learning In Developing Students’ English Skills: A Qualitative Study In Science Class - Tritias Utami, Rosanita; Dwinata, Erna (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to describe the implementation of Project-Based Learning in developing science education students’ English skills and to know their perception toward the implementation of PjBL. A qualitative approach is applied in this study. The data were gathered from six science students of a private university in Tulungagung, Indonesia, during the second semester in the academic year 2024-2025 . The result of the study revealed that PjBL positively develop students’ English skills and allows them to explore their competence. They also have better self-confidence in performing their English, especially in speaking, Project-based learning provides beneficial effects for English as Foreign Language (EFL) learners, particularly for university students since they are now demanded to be able to master communication skill both in written and spoken text since they are now demanded to be able to master communication skill both in written and spoken text.